CatM Regulation of the benABCDE Operon: Functional Divergence of Two LysR-Type Paralogs in Acinetobacter baylyi ADP1 - Ezezika, Obidimma C. (American Society for Microbiology, 2006)
Two LysR-type transcriptional regulators, BenM and CatM, control benzoate consumption by the soil bacterium Acinetobacter baylyi ADP1. These homologs play overlapping roles in the expression of multiple genes. This study focuses on the benABCDE operon, which initiates benzoate catabolism. At this locus, BenM and CatM each activate transcription in response to the catabolite cis,cis-muconate. BenM, but not CatM, additionally responds to benzoate as an effector. Regulation by CatM alone is insufficient for growth on benzoate as the sole carbon source. However, three point mutations independently increased CatM-activated benA transcription and enabled growth on benzoate without BenM. Two mutations generate variants with one amino acid change in the 303-residue CatM, CatM(V158M) and CatM(R156H). These substitutions affected regulation of benA differently than that of catB, another CatM-regulated gene involved in benzoate catabolism. In relation to CatM, CatM(V158M) increased cis,cis-muconate-dependent transcription of benA but decreased that of catB. CatM(R156H) increased effector-independent expression of catB compared to CatM. In contrast, cis,cis-muconate was required with CatM(R156H) to activate unusually high benA expression. Thus, induction by cis,cis-muconate depends on both the sequence of CatM and the promoter. A point mutation at position −40 of the benA promoter enhanced CatM-activated gene expression and altered regulation by CatM(R156H). BenM and CatM bound to the same locations on ben region DNA. The frequency with which spontaneous mutations allow CatM to substitute for BenM might predict that one regulator would be sufficient for controlling benzoate consumption. This prediction is discussed in light of current and previous studies of the BenM-CatM regulon.